Eating disorder NOS (EDNOS): an example of the troublesome "not otherwise specified" (NOS) category in DSM-IV. - Fairburn, C; Bohn, K (2005)
The "Not Otherwise Specified" (NOS) category within DSM-IV is designed for disorders of clinical severity that are not specified within broad diagnostic classes. "NOS" diagnoses are intended to be residual categories and they tend to be neglected by researchers. This can be inappropriate. The problems associated with certain NOS diagnoses are well illustrated by "Eating Disorder NOS" (sometimes termed EDNOS), which is the most common category of eating disorder encountered in routine clinical practice yet it has barely been studied. Indeed, there has been no research on its treatment. Interim and longer-term conceptual and practical solutions to the anomalous status of eating disorder NOS are proposed including the creation of a new diagnosis termed "mixed eating disorder". Several of these solutions are of relevance to NOS categories in general. All the solutions should fulfil criteria for clinical utility.